PENGARUH TINGKAT KOMPETENSI, KUALIFIKASI GURU DAN MOTIVASI TERHADAP KINERJA GURU - Kuswanto; Rachma, Evi Aulia; Youhanita, Ety; Eryadini, Ninies; Astutik, Nur Fithria Wiji (CV ODIS, 2023)
Teachers are one of the main components that support the implementation of education so to achieve professional processes and results, teachers must always improve the quality of education. However, in the field, teachers still do not implement their main duties and functions as teachers optimally. This happens because many determining factors influence this phenomenon. This research was conducted at Madrasah Ibtidaiyah Sirojul Ulum Lopang and Madrasah Ibtidaiyah Muhammadiyah Lopang involving 21 teachers. The research method uses a quantitative approach to determine the influence of competency levels, teacher qualifications, and motivation on performance. The method used is quantitative. The research results show that the level of competence shows an opposite relationship with performance. Qualifications and motivation have a significant influence on performance.